The safety and efficacy of oxaliplatin-loaded drug-eluting beads transarterial chemoembolization for the treatment of unresectable or advanced lung cancer - Bi, Yonghua; Li, Fazhong; Ren, Jianzhuang; Han, Xinwei (Frontiers in Pharmacology, 2022)
Aim: Drug-eluting beads are usually applied for the treatment of advanced hepatocellular carcinoma. Oxaliplatin was suggested as first-line therapy for advanced non–small-cell lung cancer. However, there has been little investigation about the application of drug-eluting beads transarterial chemoembolization (DEB-TACE) with oxaliplatin-loaded CalliSpheres beads (CB) for the treatment of unresectable or advanced lung cancer. We aimed to investigate the safety and efficacy of oxaliplatin-loaded DEB-TACE for the treatment of unresectable or advanced lung cancer. Methods: From January 2019 to December 2021, all patients with primary unresectable or advanced lung cancer who underwent DEB-TACE with oxaliplatin-loaded CB were retrospectively enrolled. This study defined overall survival and objective response rate (ORR) as the primary endpoints, disease control rate (DCR) and progression-free survival (PFS) as the secondary endpoints. Results: A total of 33 sessions of DEB-TACE were performed in 20 patients, with a mean of 1.7±1.0 sessions. A total of 55 arteries were emoblized by CB, including 40 bronchial arteries, 13 intercostal arteries, one suprarenal artery and one inferior phrenical artery. No procedural-related mortality or severe complications were observed. The median tumor diameter was 49.0 (Interquartile range (IQR) 37.8-66.8) mm before DEB-TACE, and decreased to 38.8 (IQR 27.7-56.9), 26.1 (IQR 19.1-48.8) and 20.5 (IQR 13.1-49.7) mm at 1, 3 and 6 months later (p=0.04). The ORR and DCR at 1, 3, and 6 months after DEB-TACE were 28.6% and 92.9%, 38.5% and 84.6%, 30.8% and 61.5%, respectively. The median PFS and median overall survival was 9.9 and 29.6 months, respectively. Conclusion: DEB-TACE with oxaliplatin-loaded CB is suggested as a safe, effective and well-tolerated treatment for patients with unresectable or advanced lung cancer.